Carotid cavernous fistula after Pipeline placement: a single-center experience and review of the literature. (5th September 2016) - Roy, Anil K; Grossberg, Jonathan A; Osbun, Joshua W; Skukalek, Susana L; Howard, Brian M; Ahmad, Faiz U; Tong, Frank; Dion, Jacques E; Cawley, Charles M
Abstract : Objective: Carotid cavernous fistula (CCF) development after Pipeline Embolization Device (PED) treatment of cavernous carotid aneurysms (CCA) can be a challenging pathology to treat for the neurointerventionalist. Methods: A database of all patients whose aneurysms were treated with the PED since its approval by the Food and Drug Administration in 2011 was retrospectively reviewed. Demographic information, aneurysm characteristics, treatment technique, antiplatelet regimen, and follow-up data were collected. A literature review of all papers that describe PED treatment of CCA was then completed. Results: A total of 44 patients with 45 CCAs were identified (38 women, 6 men). The mean age was 59.9±9.0 years. The mean maximal aneurysm diameter was 15.9±6.9 mm (mean neck 7.1±3.6 mm). A single PED was deployed in 32 patients, with two PEDs deployed in 10 patients and three PEDs in 3 patients. Adjunctive coiling was performed in 3 patients. Mean follow-up duration based on final imaging (MR angiography or digital subtraction angiography) was 14.1±12.2 months. Five patients (11.4%) developed CCFs in the post-procedural period after PED treatment, all within 2 weeks of device placement. These CCFs were treated with a balloon test occlusion followed by parent artery sacrifice. Our literature review yielded only three reports of CCFs after PED placement, with the largest series having a CCF rate of 2.3%. Conclusions: CCF formation is a known risk of PED treatment of CCA. Although transvenous embolization can be used for treating CCFs, parent artery sacrifice remains a viable option on the basis of these data. Studies support the view that adjunctive coiling may have a protective effect against post-PED CCF formation. None of the coiled aneurysms in our database or in the literature have ruptured. Follow-up data will lead to a better understanding of the safety profile of the PED for CCA.